Revisiting KH Muafi Ali Zaini's Legacy: 'Modernization' of Islamic Boarding School in Sampang - Madani, Mohammad Thoyyib; Rufaida, Rifki; Zenrif, Fauzan; Barizi, Ahmad; Zainuddin, Zainuddin (TSAQAFAH, 2024)
This study explores the transformation of Islamic boarding school education, focusing on two key aspects: revitalization and modernization. Revitalization involves renewing educational programs to enhance their effectiveness, while modernization refers to evolving the Islamic education system to improve its quality. The research aims to analyze the historical leadership of Kyai Muafi Zaini in these movements, assess community responses to the changes, and evaluate the outcomes for alumni and the broader community. Utilizing qualitative historical research methods heuristic data collection, source criticism, interpretation, and historiography the study verifies data through credibility, dependability, confirmability, and transferability checks. Findings reveal that Kyai Muafi Zaini, a prominent figure born in 1947 and deceased in 2006, played a significant role in revitalizing and modernizing Islamic boarding school education, particularly in Sampang Regency. He was a charismatic leader who established several formal educational institutions, including MTs Nazhatut Thullab and SMA Nazhatut Thullab. Through these institutions, he implemented significant transformation efforts that not only contributed to the improvement of community welfare but also played a crucial role in changing the local perception of education in Sampang. Zaini's contributions were pivotal in enhancing the quality of education in the region, as well as in shifting the negative stigma traditionally associated with Islamic education. His vision and dedication fostered a learning environment that encouraged academic excellence and personal growth. His legacy as a committed scholar and influential community leader continues to inspire and shape the educational landscape, ensuring that future generations benefit from the foundation he helped create.